Effect Of Dialium Guineense On Iron And Haematological Profiles Using Rat Models - Dadson, A.B. (University of Ghana, 2020)
ABSTRACT Background: Iron deficiency anaemia is a consequence of suboptimal dietary iron intake or inefficient dietary iron absorption. Dialium guineense also known as black velvet tamarind (BVT) has a rich combination of both iron as well as vitamin C, coupled with low levels of antinutrients. Traditionally, the fruit pulp of BVT is used to treat iron deficiency anaemia in certain parts of the Ghana. The efficacy and effectiveness of these interventions however need a wider exploration. Aim: To determine the effect of Dialium guineense pulp on iron and haematological profile levels of rats. Methods: A total of twenty SD rats were weight-matched into 4 groups of 5 rats each (Groups 1-4). Group 1 was fed on a normal diet and groups 2 - 3 fed on BVT fruit pulp in the form of fruit juice extract with different concentrations for 90 days. The rats in group 2 (low dose) were fed with 2.5 g of BVT fruit juice, with 5 g and 10 g of BVT juice for group 3 (medium dose) and group 4 (high dose) respectively. The doses of BVT were administered orally to the SD rats via gavage. Blood samples from the animals were collected by cardiac puncture at the end of the experiment. Serum iron profile (serum iron, total iron binding capacity- TIBC, percentage saturation) was performed. Additionally, haematological profile (red blood cell (RBC), haemoglobin (HB), mean corpuscular volume (MCV), mean corpuscular haemoglobin (MCH), mean corpuscular haemoglobin concentration (MCHC), white blood cell (WBC), and white blood cell differentials (neutrophils, lymphocytes, monocytes, eosinophils, basophils) were assayed using an automated haematological analyser at the end of the 90-day period. Results: The study revealed a dose dependent increase of serum iron among treatment groups, with the high dose recording the highest mean (51.93 ± 0.58 mmol/L) against the control (47.08 ± 0.58 mmol/L). There was a general decrease in TIBC among treatment groups with the medium dose group recording the lowest mean value (88.00 ± 0.50 mmol/L). A general increase in %SAT was also observed across the treatment group with the high dose group recording (52.38 ± 0.93mmol/L) against the control group (38.45 ± 0.93 mmol/L).These observations were however not statistically significant. The study showed no significant change in nearly all the haematological parameters of the research group, compared to the control group. An increase was observed in RBC with the high dose group recording (7.44 ± 0.76 × 1012/L) in contrast to the control group (7.22 ± 0.76 × 1012/L), however the difference was not statistically significant. A general decrease was observed in HB across experimental groups with the high dose group having (13.98 ± 0.42 g/dL) against the control (14.18 ± 0.42 g/dL). Furthermore, a decrease was observed across WBC values with the control having (14.18 ± 0.33 × 109/L) against the high dose group (13.60 ± 0.33 × 109/L). For WBC differentials, there was a general increase except for lymphocytes and basophils. All these differences were however, not statistically significant. A significantly strong negative correlation was observed between percent saturation and TIBC (r= -0.85, p<0.01). A significantly strong positive correlation was also observed between RBC and HBG (r= 0.72, p= 0.01) as well as MCV and MCH (r= 0.82, p <0.01). Conclusion: The findings of this study showed that Dialium guineense did not significantly increase the serum iron levels and haematological indices of the rats, although serum iron increased in a dose dependent manner.
MA in Dietetics
Keywords: Dialium guineense; haematological; Ghana; lymphocytes